Determinan Harga Saham Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Sukma Irdiana (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
Capital market is one form of financial market, where the capital market players invest in the form of securities offered by the issuer. One of the most popular securities for sale on the stock market is stock. Stocks are securities that have high profits and risks or better known as high risk and high return. High risk and high return is the higher the risk of an investment, the higher the amount of profits derived from an investment. The purpose of this study is to obtain evidence empirically and find clarity about the influence of fundamental variables consisting of ROA, EPS, NPM, DER and BVS to stock prices of companies listed in IDX period 2010-2015, either partially or simultaneously. Sample selection method used is purposive sampling and analysis model used is multiple linier regression analysis. The results showed that partially ROA, EPS, NPM, DER, and BVS have a significant effect on stock prices. Simultaneously ROA, ROE, EPS, NPM, DER and BVS simultaneously affect the stock price. Coefficient of Determination (R Square) of 48% and the rest of 52% influenced by other variables that have not been studied in this study.